The Role of Perceived Usefulness and Perceived Ease of Use in Increasing Repurchase Intention in the Era of the Covid-19 Pandemic - Raditya Ferdianto; Hendar (Research Horizon, 2022)
The COVID-19 pandemic has paralyzed many sectors, including e-commerce. Many online businesses have experienced drastic sales declines because of strict social restrictions. For this reason, e-commerce business managers need to take preventive action by further investigating what factors increase consumer purchase intentions in shopping on e-commerce so that companies can continue to survive and be sustainable. This study aims to determine the role of perceived benefits and convenience in increasing repeat purchases and the mediating role of shopping experience in influencing the relationship of benefits and convenience to repurchase online shopping users in Central Java. The sample in this study was 152 mobile shopping users in Central Java. The data collection method in this study used a questionnaire. Data were analyzed using Smart PLS 3.0 software. The results showed a positive and significant effect of perceived usefulness and perceived ease of use on the mobile consumer experience. In contrast, the consumer’s experience in mobile shopping had a positive and significant effect on repurchase intention. Repurchase intention can also be increased through consumers’ mobile experiences stimulated by perceived usefulness and ease of use.